1931
DOI: 10.1085/jgp.15.2.183
|View full text |Cite
|
Sign up to set email alerts
|

On the Rate of Oxygen Consumption by Fertilized and Unfertilized Eggs

Abstract: Measurements have been made of the rates of oxygen consumption by the eggs of several marine forms, and especially of the change in rate following fertilization. It is convenient to present some of these results separately, considering them comparatively in one of the papers and discussing the relation to other work in the field, and some of the theoretical implications. This will be done in the fourth paper (1) of this series. The present paper will be chiefly concerned with measurements on the eggs of the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1946
1946
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Once the oocyte has become a 'ripe' unfertilized egg, respiration rate falls (Borei 1948) and meiotic growth is halted (Went 1982). Depending on the species, ripe eggs may remain viable in this state for several days (Whitaker 1931;Holcomb et al 2004) and, although meiotically halted, may be far from inactive. Measurable oxygen consumption rates have been observed in unfertilized eggs for a variety of species (Whitaker 1931;Borei 1948;Horwitz 1965;Tyler, Tyler & Piatigorsky 1968;Davenport & Lonnig 1980) and may indicate the generation of energy through the Krebs Cycle.…”
Section: Egg Is Reserve Onlymentioning
confidence: 99%
See 3 more Smart Citations
“…Once the oocyte has become a 'ripe' unfertilized egg, respiration rate falls (Borei 1948) and meiotic growth is halted (Went 1982). Depending on the species, ripe eggs may remain viable in this state for several days (Whitaker 1931;Holcomb et al 2004) and, although meiotically halted, may be far from inactive. Measurable oxygen consumption rates have been observed in unfertilized eggs for a variety of species (Whitaker 1931;Borei 1948;Horwitz 1965;Tyler, Tyler & Piatigorsky 1968;Davenport & Lonnig 1980) and may indicate the generation of energy through the Krebs Cycle.…”
Section: Egg Is Reserve Onlymentioning
confidence: 99%
“…Depending on the species, ripe eggs may remain viable in this state for several days (Whitaker 1931;Holcomb et al 2004) and, although meiotically halted, may be far from inactive. Measurable oxygen consumption rates have been observed in unfertilized eggs for a variety of species (Whitaker 1931;Borei 1948;Horwitz 1965;Tyler, Tyler & Piatigorsky 1968;Davenport & Lonnig 1980) and may indicate the generation of energy through the Krebs Cycle. Unfertilized eggs contain all the necessary components of protein synthesis, including mRNAs (Tyler 1963;Tyler et al 1968) and evidence of protein synthesis has been demonstrated in ripe, unfertilized eggs of sea urchins (Tyler, Tyler and Piatigorsky 1968), clams (Bell & Reeder 1967), polychaete worms (Gould 1969) and frogs (Smith, Ecker & Subtelny 1966).…”
Section: Egg Is Reserve Onlymentioning
confidence: 99%
See 2 more Smart Citations
“…It may be pointed out moreover at this juncture that the direction of the change in b in Chaetopterus and Arbacia parallels the direction of respiratory change (oxygen uptake). Ckaetopterus exhibits a decline in rate of oxygen uptake on fertilization (Whitaker (1933)), and Arbacia shows an increase (various investigators). The parallelism between the increase in oxygen uptake and the increase in o.i.f, which occurs when the Arbacia egg is broken into halves by centrifugal force has been pointed out earlier in this paper.…”
Section: Resultsmentioning
confidence: 99%